Enhancing Offline Shopping Experiences With Real-Time Mobile Apps, Specifically in Batam City - Herman; Hernando; Fredian Simanjuntak (Universitas Ahmad Dahlan, 2026)
Information asymmetry in the offline retail market imposes substantial